ROLE OF COLOR SCHEME IN JAMINI RAI'S ART: जामिनी राय की कला में रंग योजना की भूमिका - Pandey, Shweta (International Journal of Research -GRANTHAALAYAH, 2014)
Jamini Rai produced innumerable paintings during his art journey. There is hardly any subject in this construction which could not be revealed through the paintbrush of Jamini Rai. Due to his dedication to the art and his continuity, he produced such a large number of paintings. Jamini Rai has repeated his own paintings many times, so it is very difficult to say which painting is earlier, which later, only by looking at the style, the construction period can be estimated. Apart from this, Jamini Rai never mentioned the date in his pictures, due to which the problem becomes even more complicated. Jamini Rai has made several paintings on the same subject, in which he later reconstructed some changes. In this way, during his art journey, he created many beautiful paintings based on different subjects, in which the scent of Indian soil is fragrant. Jamini Rai used canvas and oil colors to create paintings in the beginning of his art process and continued working from this mode for a long time. Gradually, with the passage of time, when Jamini Rai gave a new direction to his art journey, many changes took place in his life. He always continued new art experiments to innovate in his art. Jamini Rai voluntarily used to make changes in his art as required. जामिनी राय ने अपनी कला यात्रा के दौरान असंख्य चित्रों का निर्माण किया। इस निर्माण कार्य में शायद ही ऐसा कोई विषय हो जो जामिनी राय की तूलिका के माध्यम से प्रकट ना हो सका हो। कला के प्रति उनका समर्पण व उनकी निरन्तरता के कारण ही उन्होंने इतनी बड़ी संख्या में चित्रों का निर्माण किया। जामिनी राय ने अपने ही चित्रों को कई बार दोहराया है, इसलिये यह कह पाना बड़ा कठिन है कि कौन सा चित्र पहले का है, कौन सा बाद का, सिर्फ शैली को देखकर ही निर्माण काल का अनुमान लगाया जा सकता है। इसके अतिरिक्त जामिनी राय ने अपने चित्रों में कभी भी तिथि का उल्लेख नही किया है, इस कारण यह समस्या और भी जटिल हो जाती है। जामिनी राय ने एक ही विषय पर कई चित्रों को बनाया है जिनमें उन्होंने बाद में कुछ ना कुछ परिवर्तन करते हुए पुनः निर्माण किया। इस प्रकार उन्होंने अपनी कला यात्रा के दौरान अलग-अलग विषयों पर आधारित अनेक खूबसूरत चित्रों का निर्माण किया जिसमें भारतीय मिट्टी की सौंधी महक है। जामिनी राय ने अपनी कलायात्रा के आरम्भ में चित्रों के निर्माण कैनवास व तैल रंगों का प्रयोग किया और बहुत लम्बे समय तक इस विधा से ही कार्य करते रहे। धीरे-धीरे समय के साथ जब जामिनी राय ने अपनी कला यात्रा केा एक नई दिशा दी तब उनके जीवन में कई परिवर्तन आ गए। उन्होंने सदैव अपनी कला में नवीनता लाने के लिए नित नए कला प्रयोगों को जारी रखा। जामिनी राय स्वेच्छा से आवश्यकता के अनुसार अपनी कला में परिवर्तन किया करते थे।